2016
DOI: 10.17576/mjas-2016-2006-22
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMIZATION OF CHLOROPHYLL EXTRACTION FROM Gynura procumbens

Abstract: Gynura procumbens (Sambung nyawa) is a bicolor (green and red) herbal plant, which is widely grown in Asia. This herbs are famously used for medicinal purposes as a safe alternative to chemical-based medicine. Recent studies proved that this plant has anti-herpes simplex virus, anti-flammatory and anti-hyperglycaemic properties. This work investigates the extraction of chlorophyll a and b in Gynura procumbens using Solid liquid extraction method. The solid to solvent ratio, temperature, solvent used and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The selected optimum extraction time was 75 min. The same time behavior has been observed in a previous study [26].…”
Section: Main Effect Plotsupporting
confidence: 88%
“…The selected optimum extraction time was 75 min. The same time behavior has been observed in a previous study [26].…”
Section: Main Effect Plotsupporting
confidence: 88%
“…Finally, anti-cancer, antioxidant, and antimicrobial activities have been identified for 1-tetradecene and 1-octadene, which were found in GP ethanol extract and GP chloroform fraction, respectively (23). The volatile compounds found in GP ethanol extract, such as phytol, oleic acid, and phenol, were confirmed in a study by Abidin et al, who found five basic volatile compounds in GP ethanol extract, including 2-hexenal, phenol, oleic acid, copaene, and phytol (24).…”
Section: Discussionmentioning
confidence: 75%
“…Mohamed et al [19] investigated whether coconut shell powder together with coconut shell activated carbon composites might be used as electromagnetic interference absorption materials. In this work, basic materials such as coconut shell powder (SP) with coconut shell activated carbon (SAC) were combined with an amine hardener and an epoxy resin composite to capture microwave signals with frequencies ranging from 1 to 8 GHz.…”
Section: Properties Of Coconut Shell Powdermentioning
confidence: 99%